Traditional healers and mental illness in Uganda - Ovuga, Emilio; Boardman, Jed; Oluka, Elizabeth G. A. O. (Psychiatric Bulletin, 1999)
cross-sectional, interview survey of the beliefs, knowledge, attitudes and practice towards mental illnessof 29 traditional healers in the Pallisadistrict of Uganda was carried out. Results Many of the healers had experienced emotional problems that had been treated by other healers.Almost all had a family member who was also a traditional healer. They treated a wide range of conditions and all dealt with mental illness. Most believed that mental disorders were caused by supernatural processes. Many recognised the role of environmental agents. Their diagnosis and management of mental illness was eclectic. The healers were either traditional herbalists or spirit diviners or a mixture of both. Almost all referred patients to the district hospitals and were willing to work with government health services. Clinical implications The resultsof the survey suggest the presence of fertile ground on which to build cooperation between traditional healers and medical services. Such cooperation may harness primary care resources more effectively. Sequential or simultaneous models of collaboration (or combinations of both) may be considered. Further work on specific treatments, their outcomes and the evaluation of collaborative models is needed.
Keywords: Traditional healers; Mental illness; Uganda